A study of 1-absorbing intuitionistic fuzzy ideals of commutative semirings - Ozkan, E. Mehmet; Onar, Serkan; Ozkan, Ayten; Kaplan, Ilayda (TARU PUBLICATIONS, 2025)
The primary objective of this investigation is to offer an extensive and thorough comprehension of the characteristics, attributes, and operational tendencies inherent in 1-absorbing intuitionistic fuzzy ideals as well as 1-absorbing intuitionistic fuzzy primary ideals within the context of commutative semirings. By examining their contribution to the literature, we can gain insight into their unique characteristics and explore their potential applications in various fields. Furthermore, defining the Cartesian product of these ideals allows for a deeper analysis of their interactions and opens up new avenues for research in this area.
Keywords: 1-absorbing ideal; 1-absorbing primary ideal; 1-absorbing intuitionistic fuzzy ideal; 2-ABSORBING IDEALS; PRIME IDEALS; LATTICE; Mathematics